2007
DOI: 10.1002/pola.21817
|View full text |Cite
|
Sign up to set email alerts
|

Direct polymerization of surface‐tethered polyelectrolyte layers in aqueous solution via surface‐confined atom transfer radical polymerization

Abstract: The direct polymerization of deprotonated acidic monomers in aqueous solutions was achieved via surface-confined atom transfer radical polymerization (SC-ATRP) to produce surface-tethered polyelectrolyte brushes. Layers of poly(itaconic acid), poly(methacrylic acid), and sodium poly(styrene sulfonate) were grown by SC-ATRP from self-assembled initiator monolayers of [BrC(CH 3 ) 2 COO(CH 2 ) 11 S] 2 on gold substrates. The polymer layers were characterized with variable-angle ellipsometry and external-reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…The relationship between the grafting yield and the monomer concentration is shown in Figure 6(b). An approximately linear increase in grafting yield of the PAAc chains on the AAO-Br membranes with the AAc monomer concentration, suggest that the growth of the PAAc chains was a controlled process, which is consisted with the results reported by Sankhe et al 24 Control experiments on the pristine AAO and AAO-DOPA membranes revealed that there was no increase in graft yield when they were subjected to the ''surface initiated'' ATRP of AAc under similar reaction conditions. All of these results are consistent with the successful graft polymerization of AAc on the AAO-Br membranes via surface-initiated ATRP.…”
Section: Kinetics Of the Atrp Grafting Processsupporting
confidence: 73%
See 1 more Smart Citation
“…The relationship between the grafting yield and the monomer concentration is shown in Figure 6(b). An approximately linear increase in grafting yield of the PAAc chains on the AAO-Br membranes with the AAc monomer concentration, suggest that the growth of the PAAc chains was a controlled process, which is consisted with the results reported by Sankhe et al 24 Control experiments on the pristine AAO and AAO-DOPA membranes revealed that there was no increase in graft yield when they were subjected to the ''surface initiated'' ATRP of AAc under similar reaction conditions. All of these results are consistent with the successful graft polymerization of AAc on the AAO-Br membranes via surface-initiated ATRP.…”
Section: Kinetics Of the Atrp Grafting Processsupporting
confidence: 73%
“…The reaction solution comprised the monomer, acrylic acid (AAc, 2.88 g, 1.0 mol/L); catalyst, CuBr (2.97 mg), 2,2-Dipyridyl (4.68 mg); and 40 mL of deionized water as solvent. AAc was deprotonated by the addition of NaOH to reach a pH end point of 10.2, followed by the addition of NaCl (5.59 g), according to the protocol first proposed by Sankhe et al 24 The reaction mixture was purged with argon for 2 h in ice water bath to remove the dissolved oxygen. Polymerization was carried out at 50 C under argon atmosphere for the desired reaction time.…”
Section: Surface-initiated Atrp On the Aao-dopa Membranesmentioning
confidence: 99%
“…[31][32][33] Additionally, because light is the activating agent, SI-PMP is well suited for the direct synthesis of polyelectrolytes (PMAA, in this study), alleviating problems with, for example, catalyst complexation, dissociation, or disproportionation that occurs during ATRP of electrolytic monomers in protic media. [34][35][36][37][38] The response characteristics of the constituent materials used in this study are well known. Because of the weakly ionizable carboxylate groups along the backbone, the degree of dissociation of PMAA can be changed by adjusting the pH and/ or the ionic strength of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…This could help in designing copolymers with specific characteristics, which is a hot research field in both industrial and academic fields. In addition, this monomer as a hydrophilic monomer can shift the LCST to higher temperatures, which should be lower than the physiological temperature of 37 C for in vivo applications, and may determine the resiliency of a polymer under physiological conditions [25][26][27][28][29]. To our knowledge, no report could be found in the literature about the successful ATRP copolymerization of IA with NIPAAm [30].…”
Section: Introductionmentioning
confidence: 68%